Cyanide Insensitive Oxidase Confers Hydrogen Sulfide and Nitric Oxide Tolerance to Pseudomonas aeruginosa Aerobic Respiration - Martina R. Nastasi; Lorenzo Caruso; Francesca Giordano; Marta Mellini; Giordano Rampioni; Alessandro Giuffrè; Elena Forte (MDPI AG, 2024)
Hydrogen sulfide (H2S) and nitric oxide (NO) are long-known inhibitors of terminal oxidases in the respiratory chain. Yet, they exert pivotal signaling roles in physiological processes, and in several bacterial pathogens have been reported to confer resistance against oxidative stress, host immune responses, and antibiotics. Pseudomonas aeruginosa, an opportunistic pathogen causing life-threatening infections that are difficult to eradicate, has a highly branched respiratory chain including four terminal oxidases of the haem-copper type (aa3, cbb3-1, cbb3-2, and bo3) and one oxidase of the bd-type (cyanide-insensitive oxidase, CIO). As Escherichia coli bd-type oxidases have been shown to be H2S-insensitive and to readily recover their activity from NO inhibition, here we tested the effect of H2S and NO on CIO by performing oxygraphic measurements on membrane preparations from P. aeruginosa PAO1 and isogenic mutants depleted of CIO only or all other terminal oxidases except CIO. We show that O2 consumption by CIO is unaltered even in the presence of high levels of H2S, and that CIO expression is enhanced and supports bacterial growth under such stressful conditions. In addition, we report that CIO is reversibly inhibited by NO, while activity recovery after NO exhaustion is full and fast, suggesting a protective role of CIO under NO stress conditions. As P. aeruginosa is exposed to H2S and NO during infection, the tolerance of CIO towards these stressors agrees with the proposed role of CIO in P. aeruginosa virulence.